Karakteristik Gurita (Octopus sp.) Kering yang Dipasarkan di Pulo Aceh, Aceh Besar - Rindiani, Rindiani; Rozi, Anhar (JURNAL PERIKANAN TROPIS, 2023)
Octopus is one of the commodities caught in Pulo Aceh, Aceh Besar. The octopus catch is then traded in dry conditions. Preservation technique with drying method was carried out so as the octopus has longer life. That traditional preservation process will certainly affect the quality of dried octopus products, in which this product quality can be seen through parameters of nutritional value and microbial contamination of the product. The purpose of this study was to determine the quality of nutritional value and microbial contamination content of dried octopus products in Pulo Aceh. The method used was observation with random sampling. The nutritional value of microbes was tested using the proximate analysis method, and microbial contamination analysis used the Total Plate Number (ALT) calculation method. Based on the results of proximate analysis on dried octopus, the water content was 17.60%, the ash content was 11.55%, the protein content was 22.83%, the fat content was 4.11%, the crude fiber content was 0.11%, the carbohydrate content was 43.09%, and ALT value of 7.89 x 105 Cfu/g.